2014
DOI: 10.3319/tao.2013.08.06.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Unusual Cold-Water Intrusion in 2008 on the Catch of Coastal Fishing Methods around Penghu Islands, Taiwan

Abstract: Based upon long-term observations (1993 -2010) of satellite-derived winter sea surface temperature (SST) data, an exceptional cold-water intrusion into the southern Taiwan Strait (TS) was noted in February 2008. In the winter of 2008, La Niña caused a strong and continuous northeasterly wind that drove the cold ocean current, the China Coastal Current, more southward to penetrate the southern TS north of the Chang-Yuen Ridge. A portion of this current turned eastward to the south of Penghu Islands (PHI). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…After wind speed weakening, the SST around the Penghu Islands rose immediately, which agrees with the sequence of SST maps shown in Fig. 10d-f previous studies; e.g., Chen et al 2010;Liao et al 2013;Lee et al 2014). Through the application of the warning mechanism, the hindcast of the 2008 winter showed that a high-risk warning could precede the coldest water day by 19 days (Fig.…”
Section: Hindcasting Cold Water Dayssupporting
confidence: 88%
“…After wind speed weakening, the SST around the Penghu Islands rose immediately, which agrees with the sequence of SST maps shown in Fig. 10d-f previous studies; e.g., Chen et al 2010;Liao et al 2013;Lee et al 2014). Through the application of the warning mechanism, the hindcast of the 2008 winter showed that a high-risk warning could precede the coldest water day by 19 days (Fig.…”
Section: Hindcasting Cold Water Dayssupporting
confidence: 88%
“…The change in sign of U a in the western half of TwS (Figs. 3 and 4) means that colder surface water from the north is limited in the western half of TwS and that its interface with the current from the warmer south is likely to form a frontal region of sea surface temperature (Lee et al, 2014). This is consistent with the sea surface temperature front (Chen, 2003;Zhu et al, 2004).…”
Section: Vertically Averaged Velocity Along Ship Trackmentioning
confidence: 54%
“…Beginning in early February of 2011, the pen fishery in Penghu islands (in central TwS) suffered severe damage caused by abnormally cold water. The same damage also occurred in February 2008 (Lee et al, 2014). Comparing to the El Niño index, NINO3.4, both TwS and the eastern equatorial Pacific showed a severe decrease in sea surface temperature in early 2008 and early 2011, the La Niña years of anomalously low values of NINO3.4 relative to the period since 2001 (the full NINO3.4 series can be found at http://stateoftheocean.osmc.noaa.gov/sur/pac/nino34.php).…”
Section: China Coastal Currentmentioning
confidence: 59%
“…The observational period includes three extremely cold winters whose warning level reached high risk : , 2011: . Winter 2008 has the severest cold event over the past decade and the minimum SST (approximately 11 • C) broke the record temperature, discussed in numerous previous studies (e.g., Chen et al, 2010;Liao et al, 2013;Lee et al, 2014). Through the application of the warning mechanism, the hindcast of the 2008 winter showed that a high-risk warning could precede the coldest water day by 19 days (Fig.…”
Section: Hindcasting Cold Water Daysmentioning
confidence: 98%
“…Chang et al (2009) used satellite SST images around the Penghu Islands to show that the minimum SST (12.6 • C) in February 2008 was lower than the February climatological temperature (20 • C). The strong northeast monsoon in the winter of 2008, associated with La Niña, may drive the cold China Coastal Current to intrude more southward into the southern TS and can even suppress the northward warm Kuroshio Branch Current intruding the TS (Chen et al, 2010;Lee et al, 2014). Liao et al (2013) suggested that the cold disaster in 2008 can be divided into three stages: first, the branch of the China Coastal Current moved cold water from the western strait to the central strait; then, a strong northeast wind intensified the southwest current; and finally, cold water gradually retreated to the north due to weakened wind.…”
Section: Introductionmentioning
confidence: 99%